(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The influence of road pavement evenness on road complex functional indicators has been discovered. Classification of unevenness’s of road pavement surface according to geometric characteristics of its structure is shown. Known methods of operational quality control of road pavement evenness which application has been provided for by current regulations have been considered. Mathematical modeling of road pavement longitudinal profile with different kinds of unevenness has been conducted. On that basis the possibility of application of noted methods of operational quality control for these unevenness’s detection has been discovered.